ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMK PADA MATERI PELUANG DITINJAU DARI KEMAMPUAN AWAL MATEMATIS - Marselina, Seli; Roesdiana, Lessa (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This study was conducted to analyze the problem-solving ability of grade XII students of SMKN 2 Karawang for the 2023/2024 Academic Year in terms of their initial mathematical abilities. This research uses a qualitatively descriptive approach. The subjects consisted of six students who were selected representatively to represent each level of initial mathematical ability.  Data was collected based on problem-solving ability tests and initial mathematical ability tests. The collected data were analyzed to evaluate students' problem-solving abilities in three categories: high, medium, and low math skills. Students who have high initial mathematical abilities manage to precisely meet all indicators at each stage of problem solving. Students with moderate initial mathematical ability still do not meet the indicators at all stages of mathematical problem solving. Students with low initial mathematical ability understand all indicators but do not apply them to every solution.